2021
DOI: 10.3389/fpsyt.2021.585742
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Immune Activation and Schizophrenia–Evidence for an Immune Priming Disorder

Abstract: Schizophrenia is a complex neurodevelopmental disorder affecting around 19. 8 million people worldwide. The etiology of the disorder is due to many interacting genetic and environmental factors, with no one element causing the full spectrum of disease symptoms. Amongst these factors, maternal immune activation (MIA) acting during specific gestational timings has been implicated in increasing schizophrenia risk in offspring. Epidemiological studies have provided the rationale for this link with prevalence of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 64 publications
(55 reference statements)
0
20
0
Order By: Relevance
“…This may trigger the fetal inflammatory response syndrome (FIRS) and results in an increased cytokine level of IL-1, IL-6, IL-8, and TNF-α, which has reported an increased risk of fetal developmental abnormalities ( Gotsch et al, 2007 ). Moreover, human studies have also demonstrated a significant correlation between MIA, FIRs and the development of neurodevelopmental psychiatric disorders such as ASD, schizophrenia, neurosensorial deficits, ADHD, and psychosis in early as well as in the later period of adulthood ( Knuesel et al, 2014 ; Brown and Conway, 2019 ; Choudhury and Lennox, 2021 ).…”
Section: Altered Gut Microbiota Inflammation and Neurodevelopmental D...mentioning
confidence: 99%
“…This may trigger the fetal inflammatory response syndrome (FIRS) and results in an increased cytokine level of IL-1, IL-6, IL-8, and TNF-α, which has reported an increased risk of fetal developmental abnormalities ( Gotsch et al, 2007 ). Moreover, human studies have also demonstrated a significant correlation between MIA, FIRs and the development of neurodevelopmental psychiatric disorders such as ASD, schizophrenia, neurosensorial deficits, ADHD, and psychosis in early as well as in the later period of adulthood ( Knuesel et al, 2014 ; Brown and Conway, 2019 ; Choudhury and Lennox, 2021 ).…”
Section: Altered Gut Microbiota Inflammation and Neurodevelopmental D...mentioning
confidence: 99%
“…Although the study of Karl A. Menninger and later on the work of Torrey and Peterson were pioneering in revealing the association between viral infection and subsequent psychotic disease [6,7], it was Mednick et al (1988) who showed that maternal influenza enhances the incidence of schizophrenia in the offspring [8]. Thenceforth, similar findings have been observed with other viral (e.g., cytomegalovirus, herpes simplex virus type 2, varicella-zoster and polio), bacterial (e.g., sinusitis, tonsillitis, pneumonia, and pyelonephritis), and parasite (e.g., toxoplasmosis) infections [9,10]. In the same line, other studies have connected rubella and cytomegalovirus infection during pregnancy with increased risk of ASD in the offspring [11,12], whereas cerebral palsy in adulthood associates with maternal infections [13,14].…”
Section: Introductionmentioning
confidence: 67%
“…Prenatal insults such as maternal immune activation (MIA) and prenatal iron deficiency have been linked to schizophrenia in offspring (Canetta and Brown, 2012;Aguilar-Valles et al, 2020;Choudhury and Lennox, 2021). MIA occurs when maternal inflammation during pregnancy raises inflammatory markers to above the normal range.…”
Section: The Neurodevelopmental Hypothesis Of Schizophreniamentioning
confidence: 99%